KNOWLEDGE, ATTITUDE AND PRACTICE OF COMMON COLD AND ITS MANAGEMENT AMONG DOCTORS OF PAKISTAN - Rehman, Muneeb ur; Tariq, Naseer Alam; Ahmed, Mamoon; Ahmad, Maryam; Zahid, Areej; Chaudhry, Quratulain; Tahir, Bisma; Islam, Zoraiz Ul; Mohi Ud Din, Zahoor (Journal of Ayub Medical College Abbottabad, 2016)
Background: Antibiotic misuse for upper respiratory tract infections such as the common cold is widespread in clinical practice. Excessive prescription of antibiotics by doctors has resulted in increased antimicrobial resistance. This led to our objective of determining the percentage of doctors in Pakistan prescribing antibiotics for the treatment of common cold and to know about their knowledge in preventing the spread of this disease. Methods: It was a cross-sectional descriptive study, conducted in 9 cities of Pakistan including Rawalpindi, Islamabad, Peshawar, Lahore, Karachi, Faisalabad, Sargodha, Multan and D.G. Khan over a period of 03 months -from October to December, 2013. Questionnaire regarding the disease spread and its treatment was distributed among 300 randomly selected doctors in nine cities of Pakistan from both public and private sector. Results: Eighteen percent of the doctors prescribe antibiotics for common cold. Only 113 (37.7%) doctors correctly responded that mean incubation period for common cold was 1-2 days. Two hundred and nine (69.7%) answered correctly that cold weather increases susceptibility to common cold. Only 84 (28%) responded correctly by choosing that regular and frequent hand-washing with good quality soaps was the most effective way to prevent spread of this disease in day-to-day life. Conclusion: Antibiotics are being prescribed for treatment of common cold by a large proportion of doctors. There is insufficient knowledge among our doctors regarding the factors which aggravate or alleviate common cold symptoms as well as the methods by which these infections can be prevented. Keywords: Antibiotics, Antimicrobial Resistance, Common Cold, Upper Respiratory Tract Infections (URTIs), Viruses